Needs Analysis of Assosiateds Nurses RSUD Aceh Tamiang Year 2018 - Carlis, Yun (Sari Mutiara Indonesia University Press, 2018)
The mismatch number of nurses with calculation of hospital needs is a problem that should examine at hospital, such as the researcher should determine the real nurse workload. Kind of this research is the analytic observational research which aims to analyze the nurse workload and the executive nurse needs at the ward and the specialunit of RSUD Aceh Tamiang. This research used time and motion study method approach and the calculation of WINS formula (workload Indicator of Staff Needs). The sample of this research is all of the population as many as 280 people. The result of this research showed us;the average of productive workload of executive nurses at ten wars, such as Teuku Umar Ward, Cut Mutia Ward, VVIP Ward, Muda Sedia Penyakit Dalam Ward, Muda Sedia Bedah Ward, Iskandar Muda Ward, ICU, Operation Room (OK), IGD and Haemodialisa ward in the medium category (81%). The result of personel calculation needs with WISN method showed us the totals of executive nurse are excessive at RSUD Aceh Tamiang. The score of this ratio is 1,38, it means that the ratio > 1. According to WISN, the executive nurse needs is 204 people but the personnel that is in in the field as many as 280 people at the ward and the special unit of RSUD Aceh Tamiang. This case showed us, there is the excessive of executive nurse as many as 76 people.